2017
DOI: 10.1194/jlr.d076190
|View full text |Cite
|
Sign up to set email alerts
|

Diastereomer-specific quantification of bioactive hexosylceramides from bacteria and mammals

Abstract: Mammals synthesize, cell-type specifically, the diastereomeric hexosylceramides, β-galactosylceramide (GalCer) and β-glucosylceramide (GlcCer), which are involved in several diseases, such as sphingolipidosis, diabetes, chronic kidney diseases, or cancer. In contrast, , a member of the human gut microbiome, and the marine sponge,, produce α-GalCer, one of the most potent stimulators for invariant natural killer T cells. To dissect the contribution of these individual stereoisomers to pathologies, we establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 85 publications
(91 reference statements)
3
43
0
Order By: Relevance
“…This supports the notion that C24:1-GlcCer, or more complex GSLs, are the major self-antigens required for i NKT cell development in the thymus and that lack of VLC-SLs in CerS2 null antigen-presenting DP thymocytes leads to reduced levels of i NKT cells. Concerning the anomeric configuration, previous studies have suggested that an α-linked monoglycosylceramide with a C24:1 acyl chain might be an endogenous ligand of i NKT cells ( 4 ), although the existence of α-GlcCer in mammals is still somewhat controversial ( 5 , 14 ) whereas C24:1-β-GlcCer is found at high levels in mouse thymus ( 63 ). Our data showing lower levels of VLC-GlcCer, concomitant with lower levels of i NKT cells, suggest that VLC-GlcCer, or complex VLC-GSLs, act as the endogenous self-antigens presented by CD1d molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the notion that C24:1-GlcCer, or more complex GSLs, are the major self-antigens required for i NKT cell development in the thymus and that lack of VLC-SLs in CerS2 null antigen-presenting DP thymocytes leads to reduced levels of i NKT cells. Concerning the anomeric configuration, previous studies have suggested that an α-linked monoglycosylceramide with a C24:1 acyl chain might be an endogenous ligand of i NKT cells ( 4 ), although the existence of α-GlcCer in mammals is still somewhat controversial ( 5 , 14 ) whereas C24:1-β-GlcCer is found at high levels in mouse thymus ( 63 ). Our data showing lower levels of VLC-GlcCer, concomitant with lower levels of i NKT cells, suggest that VLC-GlcCer, or complex VLC-GSLs, act as the endogenous self-antigens presented by CD1d molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivity to α-GalCer is used to define i NKT cells and distinguishes them from other NKT subsets ( 3 ). Most mammalian GSLs exist as β anomers although there is some evidence that mammalian α-linked glycosylceramides are also found ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the M+2 isotopic component of HexCer(d18:1/24:1) will interfere with the quantification of HexCer(d18:1/24:0), especially when the former exists at much higher abundance. More recently, the hydrophilic interaction chromatography (HILIC) method has gained popularity in GlcCer and GalCer separation (44)(45)(46). Particularly worth noting is the development of a novel HILIC method using a more hydrophobic starting solvent to allow not only baseline resolution of GlcCer and GalCer with great detection sensitivity [LLODs of 2 and 7 ng/ml for GlcCer and GalCer, respectively, which is similar to the LLODs of 3 nM or 2.4 ng/ml for HexCer(d18: 1/24:1) reported using our method] but also separation of and -anomers (46).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the hydrophilic interaction chromatography (HILIC) method has gained popularity in GlcCer and GalCer separation (44)(45)(46). Particularly worth noting is the development of a novel HILIC method using a more hydrophobic starting solvent to allow not only baseline resolution of GlcCer and GalCer with great detection sensitivity [LLODs of 2 and 7 ng/ml for GlcCer and GalCer, respectively, which is similar to the LLODs of 3 nM or 2.4 ng/ml for HexCer(d18: 1/24:1) reported using our method] but also separation of and -anomers (46). The added capability of this improved version of the HILIC method may be important because gut microbiota have been shown to produce -GalCer that may appear in plasma under pathological conditions (46,47) and thus should be differentiated from the normal -anomers.…”
Section: Discussionmentioning
confidence: 99%
“…60 In addition to B. fragilis, Prevotella copri and Bacteriodes vulgatus, two other commensals belonging to the Bacteriodetes phylum, express iNKT cell antigens, although at approximately 100-fold lower concentrations than B. fragilis. 61 Within the Firmicutes phylum so far only the commensal strain Lactobacillus casei has been described to express an iNKT cell antigen. 62 Furthermore, a few other reports reported iNKT cell antigens from commensal bacteria, without clearly defining the source 48 or the exact structure of the antigen (e.g.…”
Section: (3) Mucus Production and Glycosylationmentioning
confidence: 99%